Direct and indirect costs of nonfatal road traffic injuries in Iran: A population-based study. (19th May 2017) - Karimi, Hasti; Soleyman-Jahi, Saeed; Hafezi-Nejad, Nima; Rahimi-Movaghar, Afarin; Amin-Esmaeili, Masoumeh; Sharifi, Vandad; Hajebi, Ahmad; Saadat, Soheil; Akbari Sari, Ali; Rahimi-Movaghar, Vafa
ABSTRACT: Objectives : The objective of this study was to assess the incidence rate as well as direct and indirect costs of nonfatal road traffic injuries (RTIs) in Iran in 2011. Methods : Data from the 2011 national household survey were used. In this survey, data on demographics, history, and costs of injury were obtained in 2 steps: first, direct face-to-face interview and second, telephone calls. We estimated the incidence rate of nonfatal RTIs in this year. The direct costs included medical care as well as nonmedical costs paid by the patient or insurance services. The indirect costs were estimated by considering the cost of absence from work or education. We also used logistic regression analyses to investigate risk factors of nonfatal RTIs. Results : We found 76 nonfatal RTI cases (0.96%) out of 7, 886 whole reference study cases. These 76 injured patients had a history of RTI in the preceding 3 months. The annual incidence of RTIs was estimated at 3.84%. The mean age of RTI cases was 28.5 ± 10.6 and 88.16% of them were male. Male gender was a major risk factor (odds ratio [OR] = 9.64, 95% confidence interval [CI], 4.79–19.41) and marriage was a protective factor (OR = 0.44, 95% CI, 0.28–0.70) for RTI. The medians of direct, indirect, and total costs were US$214, US$163, and US$387, respectively. The total cost of nonfatal RTIs in Iran was estimated at 1.29% of the gross domestic product (GDP) in 2011. Conclusions : In Iran, nonfatal RTIs imposed a total cost of almost US$7 billion to the country for one year. Extension and more serious implementation of preventive measurements seem necessary to decrease this notable burden of RTIs.